2021
DOI: 10.1039/d1cc01185e
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline assembly of metal–organic polyhedra driven by ionic interactions with polyoxometalates

Abstract: Charge-driven self-assembly of cationic zirconium-based metal-organic polyhedra (MOPs) with polyoxometalates (POMs) lead to a series of porous crystalline salts, prepared by simple mixing of soluble precursors. Reactivity of immobilized POMs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Some initial studies have shown that this can be achieved by designing mutual coordination bonds between two different cages; 65 using ionic interactions based on charged MOCs to form MOC-based salts; 66 and mixture of charged MOCs with other molecular species such as polyoxometallates. 67 The possibility of forming molecular salts suggests this approach could be applied to other functional ionic components. Additionally, complexity can be integrated into the same cage by using a multivariate linker strategy, where a controlled ligand diversity leads to different photophysical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Some initial studies have shown that this can be achieved by designing mutual coordination bonds between two different cages; 65 using ionic interactions based on charged MOCs to form MOC-based salts; 66 and mixture of charged MOCs with other molecular species such as polyoxometallates. 67 The possibility of forming molecular salts suggests this approach could be applied to other functional ionic components. Additionally, complexity can be integrated into the same cage by using a multivariate linker strategy, where a controlled ligand diversity leads to different photophysical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The chloride anions in HOFs can be replaced by anionic MOCs to form doubly porous salts, which retain high stability and solubility. , The anionic porous cuboctahedral [Cu 24 (SO 3 -bdc) 24 ] 24– cage was employed to stabilize the cationic porous tetrahedral [Zr 12 (μ 3 -O) 4 (μ 2 -OH) 12 (Cp) 12 (Me 2 -bdc) 6 ] 4+ cage, affording a quantitative yield of pure-phase porous salt. The polyoxometalates (POMs) can also be mixed with chloride ions to produce POM-MOC porous salts with enhanced electronic properties …”
Section: Hierarchical Self-assembly Of Zr-mocsmentioning
confidence: 99%
“…The polyoxometalates (POMs) can also be mixed with chloride ions to produce POM-MOC porous salts with enhanced electronic properties. 28 Unlike fragile tetrahedral Zr-MOC frameworks that undergo structural rearrangement upon solvent removal, cubic Zr-MOCs with eight SBUs can impart reinforced O−H•••Cl•••H−O interactions and microporosity, resulting in highly stable HOFs. 14 In this aspect, we assembled D-camphoric acid (H 2 D-cam) with zirconocene dichloride to afford a chiral HOF with V 8 E 12 topology (Figure 8).…”
Section: Hierarchical Self-assembly Of Zr-mocsmentioning
confidence: 99%
See 1 more Smart Citation
“…[110] Interestingly, Ohba et al used a similar strategy to demonstrate that bulky counter-ions could be used to control assembly of charged MOPs. [111] They assembled Me 2 -ZrMOP with the polyoxometalates (POMs) of the formula [SiW 12 O 40 ] 4− . Consistent with the charge of each building block, the resultant POM-MOP crystalline assembly has a MOP/POM ratio of 1:1.…”
Section: Assembly Of Mops Through Supramolecular Non-coordinative Bondsmentioning
confidence: 99%